Membrane Electrolysis of Borax Pentahydrate (Na(2)B(4)O(7 center dot)5H(2)O) - (:unkn) unknown (ELECTROCHEMICAL SOC INC, 2012)
In the present work, membrane electrolysis of nearly saturated borax solution prepared from borax pentahydrate (Na(2)B(4)O(7 center dot)5H(2)O) was studied. Mono layer cation-exchange membrane (Nafion 551) was used as a separator in a two-compartment electrolysis cell for the production of sodium hydroxide and boric acid. The anolyte concentration was adjusted in order to obtain a Na2O/B2O3 mol ratio of 0.1 by dissolving boric acid and borax pentahydrate together. Experiments were performed in continuous operation mode by feeding nearly saturated borax solution. The effects of different catholyte concentrations (10, 20, and 30% NaOH) on the current efficiency and the specific energy consumption were calculated and the quality of boric acid products was determined. (C) 2012 The Electrochemical Society. [DOI: 10.1149/2.012209jes] All rights reserved.
Keywords: BORIC-ACID